In vitro Ploidy Manipulation for Crop Improvement - Touchell, Darren H.; Palmer, Irene E.; Ranney, Thomas G. (Frontiers in Plant Science, 2020)
In vitro regeneration systems provide a powerful tool for manipulating ploidy to facilitate breeding and development of new nursery and bioenergy crops. The development of polyploids can expand breeding opportunities, assist with the development of seedless triploid cultivars, enhance ornamental characteristics and environmental tolerances, and restore fertility in wide hybrids. In vitro ploidy manipulation is commonly induced using antimitotic agents such as colchicine, oryzalin and trifluralin. Successful induction requires efficient penetration of the antimitotic agent and may be dependent the length of exposure and concentrations of antimitotic agents, tissue types, and interactions with basal media and plant growth regulators. At the Mountain Crop Improvement Lab, in vitro ploidy manipulation has been an integral component of our nursery and bioenergy crop breeding program on a diverse range of taxa including Miscanthus, Rudbeckia, Hypericum, Hydrangea, Rhodendron, and Acer. In vitro conditions vary among taxa and individual genera, species, and cultivars, often requiring unique treatments to optimize polyploid induction. In some taxa, the induction of polyploidy influences in vitro growth, development, and root formation. Here we provide an overview of the application of in vitro ploidy manipulation for ornamental and bioenergy crop breeding and improvement.